Vocational education and training at higher qualification levels - (:unkn) unknown (Publications Office of the European Union, 2011)
"The European policy agenda within the Copenhagen and the Bologna processes calls for an increase in qualification levels of the working population. The European qualifications framework and the European credit system for vocational education and training operate at all qualifications levels. What are the characteristics of vocational training offers for higher qualifications? What is the nature of those qualifications? Which governance patterns are in place? This research paper seeks to identify offers across boundaries of well-established education and training sectors (VET and HE) and for overcoming the institutional divide. It deals with scientific discussions on academisation and vocationalism, reviews definitions in use and discusses current developments and understanding in policy and practice. Deliberate choice was made to analyse VET at higher qualification levels in 13 European countries and six case studies in different fields. This illustrates diversity and sustainability in provision of qualifications. The evidence gathered is a starting point for defining further steps in policy, practice and research." (Hrsg., BIBB-Doku)
Keywords: S 2.2.4 Anrechnung, Prüfung & Zertifizierung; S 1.4 Hochschulbildung; G 1.2.3 Qualifikationsentwicklungen; I 2.2 Europa; Gleichwertigkeit; Allgemeinbildung; Berufsbildung; Qualifikationsniveau; Hochschulbildung; Akademisierung; Fallbeispiel; Europa